Social sustainability and genetic biodiversity in Peruvian alpaca production: a review - Julia Bello-Bravo; Denis Pilares; Luiz F. Brito; Alejandra M. Toro Ospina; Luis P. B. Sousa Junior; Gerardo Cornelio Mamani Mamani; Jon Schoonmaker; Jennifer Richardson (Pastoralism)
This conceptual review addresses the social sustainability challenges facing traditional alpaca pastoralism in Peru, particularly in light of economic and environmental interventions such as selective breeding for international market demands. While efforts to prioritize economic and environmental sustainability are well-documented, the neglect of social sustainability threatens the survival of traditional Andean knowledge, practices, and cultural resilience. Utilizing a triple-bottom-line framework, this review explores the social impacts of genetic biodiversity conservation efforts within the Peruvian alpaca value chain. It highlights how selective breeding, driven by global market preferences, risks eroding not only the genetic diversity of alpacas but also the sustainability of traditional herding practices. The review underscores the need for increased attention to social dimensions when implementing technical solutions to economic and environmental challenges, emphasizing the preservation of indigenous knowledge systems and practices to sustain the livelihoods and cultural heritage of alpaqueros. Recommendations include prioritizing social sustainability by integrating traditional practices into development agendas, fostering greater participation from indigenous communities, and encouraging the transmission of intergenerational knowledge to ensure the long-term viability of Peruvian pastoralism. Future research directions are also discussed.